Natural Products for Targeting Acanthamoeba spp. - Yassmin, Isse Wehelie *; Aishath, Leesha Nasih *; Ayaz, Anwar *; Siddiqui, Ruqaiyyah; Maciver, Sutherland; Khan, Naveed Ahmed (Bentham Science Publishers, 2022)
Pathogenic Acanthamoeba is responsible for causing serious eye and fatal brain infections. A successful prognosis remains elusive despite advances in chemotherapeutics and supportive care. Natural products of medicinal value remain a promising source for drug development due to their broad-spectrum antimicrobial activities. Herein, we discuss anti-Acanthamoebic properties of natural products originating from plants, marine, and microbial sources that could be exploited as a potential avenue for drug discovery against infections caused by Acanthamoeba.